Dangerous Pollutants (Xenobiotics) in Urban Water Cycle - Hlavinek, Petr.; Bonacci, Ongjen; Marsalek, Jiri.; Mahrikova, Ivana; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Growing population and rising standards of living exert stress on water supply and the quality of drinking water. Some of these pressures can be reduced by demand management and water and wastewater reuse. In wastewater ma- gement, new challenges are caused by new chemicals of concern, including endocrine disrupters, pharmaceuticals, hormones, and personal care products, which often pass through wastewater treatment plants unabated, but may cause serious impacts on receiving aquatic ecosystems. The topics focused on evaluation of impact of xenobiotics in the whole Urban Water Cycle are an interdisciplinary task which has a rising concern these days. Xenobiotics includes both inorganic elements like heavy metals, metalloids and man-made organic compounds such as pesticides, surfactants, solvents, fragrances, flavours, and pharmaceuticals as well as endocrine dis- pters. It has been estimated that 70,000 xenobiotics may potentially be hazardous for humans and/or ecosystems. Water supply, urban drainage and wastewater treatment systems were originally designed to solve just conventional problems such as supply of potable water, flooding prevention and sanitation. The main problem within the conventional urban water cycle approaches is absence of design to deal with xenobiotics. Nowadays can be seen increased focus on rainwater use, wastewater reclamation and reuse in industrial and as well in domestic sector what increase the exposure to xenobiotics.
Challenges In Water Resources Management -- A Whole-Life Cost Approach To Sewerage And Potable Water System Management -- Reuse Of Urban Water: Impact Of Product Choice -- Urban Water Resources Management In Romania - Perspectives For The Sustainable Development In Order to Supply Water to Human Settlements -- Water Quality And Wastewater Treatment Systems In Georgia -- Stormwater Management In Urbanised Areas -- Safety And Security Of Water Supply And Sanitation -- Small Urban Rivers Of Chernivtsi: Level Of Organic Pollutants Content, Main Sources And Effective Green Solutions -- Reconstruction And Rehabilitation Of Sewer Systems In Slovakia -- Waste Water Treatment From Small Urban Areas -- Allium-Assay In Evaluation Of Drinking And Surface Water Mutagenicity -- Modelling Water Quality For Integrated Water Resources Management At The Basin Scale -- Xenobiotics And Its Treatment, Impact Assessment -- Polar Organic Micropollutants In The Water Cycle -- Pharmaceuticals And Personal Care Products (Ppcp) In Canadian Urban Waters: A Management Perspective -- Viruses In Ground Water -- Ecohydrology Of Dojran Lake -- Polychlorinated Biphenyls In Urban Environment Of Belarus: Sources, Pollution, Problems Of Monitoring -- Phytotoxicity Assessment Of Effluent Waters, Surface Water And Sediments -- Monitoring And Modelling Pesticide Dynamics In Surface Water -- Methods For Toxicity Testing Of Xenobiotics In Wastewater Treatment Plants And In Receiving Water Bodies -- Chromium And Atrazine Contamination Of The Ljubljansko Polje Aquifer -- Wastewater Treatment And Reuse -- Cost Modelling In Waste Water Treatment Processes: An Empirical Analysis For Spain -- Review On The Assessment Of The Removal Efficiency Of Wastewater Treatment Plants For Selected Xenobiotics -- Poster Section -- Aqueous Photocatalysis, Natural Organic Matter Characterization And Removal: A Case Study Of The Photacatalytic Oxidation of Fulvic Acid -- Chemical And Ecological Problems Of Small Reservoirs At Designing Of Wastewater Treatment Installations -- Facts, Contradictions And Possible Improvement Actions For Hazardous Wastewater Management - A Case Study -- Complex Kinetic Indexes For Estimation Of Surface And Waste Water Quality -- Continually Measured Orp And Ph Signal For Control Of Nitrogen Removal -- Operation Of Domestic Wastewater Treatment Plant With Submerged Membrane Modules -- The Comparative Study Of The Overall Effect Of Crude Oil On Fish In Early Stages Of Development -- Evaluation Of Vilnius City (Lithuania) Snow Pollution Toxicity By Use Of Fish Biotests -- Minimization Of Dangerous Pollutants In The New Sanitation Concept For Separation Treatment Of Wastewater -- Pollution Of Ground Sources Of Drinking Water With Technogenic Tritium.
Keywords: Water pollution; Water quality; Biochemistry; Ecotoxicology; Civil engineering; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Quality/Water Pollution; Biochemistry, general; Ecotoxicology; Civil Engineering